T cell subsets in HIV infected patients after successful combination antiretroviral therapy: impact on survival after 12 years. - Frederikke Falkencrone Rönsholt (Public Library of Science (PLoS), 2012)
Objectives Immune activation is decreased by combination antiretroviral therapy (cART) in patients infected with human immunodeficiency virus (HIV), but residual activation remains and has been proposed as a cause of premature aging and death, but data are lacking. We analyzed the relationship between T-cell subsets after 18 months of cART and overall survival during 12 years of follow up. Methods A cohort of 101 HIV infected patients who had undetectable plasma HIV after starting cART was included in 1997-1998. T cell subsets were analyzed by flowcytometry after 18 months of cART. Relation to survival was calculated using Kaplan-Meier curves and multiple Cox regression. Results Seventeen patients died during the observation period. The leading causes of death were non-AIDS cancer and cardiovascular disease. Higher levels of CD8 memory T cells (CD8+,CD45RO+,CD45RA-) showed a significant beneficiary effect on survival, HR of 0.95 (95% confidence interval 0.91-0.99, P = 0.016) when adjusted for age, nadir CD4 count, CD4 count, and AIDS and hepatitis C status. T cell activation was not associated with increased risk of death. Conclusions Larger and longitudinal studies are needed to accurately establish prognostic factors, but overall results seem to suggest that prognostic information exists within the CD8 compartment.